Designing a Competitive Digital Marketing Model in Mashhad Leather Industry - Khajavi Dehshib, Fahime; Ghafourian Shagerdi, Amir; Shoujaei Baghini, Golnar; Rostami, Mohammad Reza (Business, Marketing, and Finance Open, 2026)
The present study aimed to design a competitive digital marketing model in Mashhad leather industry. This study employed a qualitative approach to research. The research population in the qualitative phase included experts and managers of leather industry in Mashhad, of whom ten were selected purposively and non-randomly. The main data collection instrument was a semi-structured in-depth interview. A qualitative data analysis was conducted based on the grounded theory. According to the paradigmatic model designed, the components of digital marketing in Mashhad leather industry could be divided into six categories: causal factors (digital marketing strategy, personalization and interactions), contextual conditions (participation, social media, human resources, digital marketing ecosystem), central phenomenon (digital marketing mix), strategies (digital culture, social and ecological factors, technological factors), intervening conditions (internal factors, external factors, competitive environment), and outcomes (customer satisfaction, customer loyalty, customer attraction and retention). The results show the significance of digital marketing mix in the leather industry for growth and development in the online market, which can potentially affect the success of leather industry, which requires digital marketing facilities and infrastructure.